Investigation of the family approach to weight and eating for families affected by cancer cachexia. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Hopkinson, Jane
Abstract : Background: Weight loss and anorexia are symptoms of cancer cachexia syndrome. They are experienced by up to 80% of patients with advanced cancer and can be distressing for both patients and their family members. A Post Doctoral Fellowship funded by Macmillan Cancer Support (2008–11) has enabled the development of the first psycho-educational family intervention for cachexia-related problems: the Family Approach to Weight loss and Eating (FAWE). Aim: To report a Phase I proof of concept study of FAWE, with scope as defined by the Medical Research Council's guidelines for developing a complex intervention. Methods: The study was a mixed-methods investigation of the acceptability and feasibility of FAWE, including observation of its benefits and potential harms. The study protocol was completed by 16/20 purposively selected patient-family carer community-dwelling dyads in the South of England in 2010/11. Research interviews, which included the FAWE intervention, were of 30–135 min duration (median 72 min) and conducted in the dyads' homes. A User Involvement Group (consumers, dietitians, clinical psychologists, nurses specialists, family therapists and academics) were engaged across the course of the study, so that expert opinion informed data analysis and refinement of the FAWE intervention. Results: The patient-family carer dyads comprised seven female and nine male patients (age range 41–84 years) and their carers. The techniques used in the three step FAWE intervention were observed to facilitate the intended talk, without apparent adverse consequences. Patient-family carer dyads were found accepting of and to express satisfaction with a nurse delivered intervention that provides both information about eating well with cancer cachexia and that aids perspective taking, talk about food and feelings and talk about how family members help each other with cachexia-related problems. Conclusion: FAWE should now be tested in a pilot trial for effect on emotional health outcomes in patients and their family carers.